PENGEMBANGAN MEDIA AUDIO VISUAL BERBASIS APLIKASI CANVA UNTUK MENINGKATKAN KETERAMPILAN MENGANALISIS INFORMASI IKLAN DAN KATA KUNCI KELAS V SD - Desita Putri, Cindi Arjihan; Laila, Alfi; Damariswara, Rian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research and development aims to support Indonesian language learning of advertising materials and advertising keywords. The subjects of this research consisted of two teaching staff and 44 class V students at SD Negeri Kutorejo 2. This research used the Research and Development (R&D) research methodology. The steps for developing audio visual media based on the Canva application use the ADDIE model development procedure (Analysis, Design, Development, Implementation, and Evaluation). Media validity was obtained from media experts at 82% (very valid) and material experts at 92% (very valid). The effectiveness of the media was obtained based on limited scale trials of 83% (very effective) and wide scale trials of 87% (very effective). The practicality of the media was obtained through a questionnaire regarding the responses of students and class V educators at SD Negeri Kutorejo 2 to audio visual media based on the Canva application. The results of the questionnaire responses from class V students at SD Negeri Kutorejo 2 were 86% (very practical) responses from teaching staff and 91% (very practical) responses from students.